Gender difference in anxiety and related factors among adolescents - Chengzhen Bao; Lili Han (Frontiers in Public Health)
BackgroundAnxiety is widespread among adolescents, and research has shown that this condition can profoundly affect their mental, emotional, and physical well-being. The purpose of this study was to analyze gender differences in anxiety levels among adolescents and to explore the influencing factors and pathways.MethodsA total of 3601 adolescents were included in this study (age: 15.14±1.97 years; male: 48.76%). Gender, age, school category, grade, duration of sleep, duration on Internet, anxiety and several social factors were investigated by online questionnaire. Teachers were responsible for organizing students to fill out the questionnaire. The Generalized Anxiety Disorder (GAD-7) was applied to measure participants’ anxiety levels over the past 2 weeks. An Ordinal Logistic Regression measured risk factors of anxiety, while a path analysis was used to estimate the structural relationship between risk factors and anxiety.ResultsThe severity of anxiety in female was higher. Approaching graduation, lack of sleep, poor peer relationships, poor ability to complete tasks, and unwillingness to seek help when in a bad mood were risk factors for anxiety in both male and female adolescents. Among female, prolonged Internet access is a risk factor for anxiety. The fit indices for the modified models were appropriate (male: GFI=0.999, IFI=0.996, TLI=0.976, CFI=0.995, AGFI=0.990, RMSEA=0.021, SRMR=0.016; female: GFI=0.997, IFI=0.990, TLI=0.971, CFI=0.990, AGFI=0.990, RMSEA=0.020, SRMR=0.018).ConclusionThe female adolescents might have higher levels of anxiety, that academic stress, sleep, peer relationships, competence, and level of social support might be influence factors on anxiety in adolescents, and that “daily duration on Internet” might not be the risk factor in male adolescent.